Radioresistant Sf9 insect cells undergo an atypical form of Bax-dependent apoptosis at very high doses of γ-radiation. (December 2013) - Chandna, Sudhir; Suman, Shubhankar; Chandna, Mauli; Pandey, Akshay; Singh, Vijaypal; Kumar, Ashish; Dwarakanath, Bilikere Srinivasarao; Seth, Rakesh Kumar
Abstract Purpose: To investigate the underlying mechanisms of cell-death at extremely high doses of radiation in radioresistant Spodoptera frugiperda-9 (Sf9) insect cells. Materials and methods: Morphology, cell proliferation and DNA-fragmentation analysis was performed at 500–2000 Gy. Changes in intracellular reactive oxygen species (ROS), mitochondrial membrane potential (MMP), cardiolipin oxidation and Annexin-V externalization were studied using flow-cytometry. Cytochrome-c release was measured using immunofluorescence microscopy. Inhibitors of apoptosis, i.e., Bongkrekic acid (BKA), Caspase-9 inhibitor (C9i), 5-(4-fluorosulfonylbenzoyl) adenosine hydrochloride (FSBA) and Cyclosporin-A (CsA) were used to dissect apoptotic mechanism at many classical steps. Caspase-3 activity was measured using a caspase-activity assay kit. Results: A dose-dependent induction of typical apoptosis was observed at extremely high doses, marked by extensive apoptotic body formation. However, certain atypical responses such as cellular hypertrophy and the lack of phosphatidylserine-externalization were observed during the initial hours after radiation. Loss of mitochondrial membrane potential observed at 48 h following a 2000 Gy dose was accompanied by an increase in ROS that caused significant cardiolipin oxidation leading to cytochrome-c release, caspase activation and internucleosomal DNA fragmentation. Inhibitors of B-cell lymphoma-2 (Bcl-2)-associated X protein (Bax)-mediated cytochrome-c release, apoptosome formation and caspase-9 effectively prevented radiation-induced apoptosis, strongly suggesting the role of Bax-dependent cell death mechanism. Conclusions: Our study demonstrates that the Sf9 insect cells display good homology with human cells in the mitochondria-dependent events during radiation-induced apoptosis, although doses eliciting similar responses were 50–200 times higher than human cells. Factors upstream to mitochondrial damage remain pertinent for a thorough understanding of this extreme radioresistance displayed by lepidopteran cells.